2019
DOI: 10.3892/ol.2019.10832
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radioactive 125I on apoptosis of HGC-27 gastric cancer cells

Abstract: Effects of radioactive 125I particles at different doses on apoptosis of HGC-27 gastric cancer cells were investigated. HGC-27 gastric cancer cell suspension was used to establish a tumor-bearing mouse model. The model was reared for approximately 3 weeks and then divided into the control group (implanted with blank particles), the low dose group (implanted with 1.48×10−7 Bq 125I particles), the medium dose group (implanted with 2.22×10−7 Bq 125I particles) and the high dose group (implanted with 2.96×10−7 Bq … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“… 33 125I particles also can inhibit the growth of HGC-27 gastric cancer cell transplants and promote the expression of Bax, caspase-3, and caspase-8 mRNA in the tumor tissue. 34 These studies had confirmed that 125 I seed brachytherapy could inhibit the proliferation and promote the apoptosis of cells. 35 So when 125 I seeds are implanted in the lesions of NSCLC, persistent low-dose irradiation could affect the different stages of cell cycle, which could continue to kill tumor cells.…”
Section: Discussionmentioning
confidence: 92%
“… 33 125I particles also can inhibit the growth of HGC-27 gastric cancer cell transplants and promote the expression of Bax, caspase-3, and caspase-8 mRNA in the tumor tissue. 34 These studies had confirmed that 125 I seed brachytherapy could inhibit the proliferation and promote the apoptosis of cells. 35 So when 125 I seeds are implanted in the lesions of NSCLC, persistent low-dose irradiation could affect the different stages of cell cycle, which could continue to kill tumor cells.…”
Section: Discussionmentioning
confidence: 92%
“…erefore, (125)I particle implantation can produce a high dose at the site, while the radiation dose of surrounding normal tissues is low, with highly conformal radiation [13][14][15]. Zhao et al found that (125)I seed implantation based on CT-guided 3D template-assisted technique can Evidence-Based Complementary and Alternative Medicine effectively alleviate the tumor and improve the survival rate in patients with refractory malignant tumors [16].…”
Section: Discussionmentioning
confidence: 99%